Rethinking benefit sharing in collaborative human genetic research from an Afrocommunitarian perspective - Ewuoso, Cornelius; Sudoi, Allan; Kamuya, Dorcas (Frontiers in Genetics, 2022)
This article draws on reflections about humanness, friendliness and partiality, in the writings of Afro-communitarians to develop principles for thinking critically about why benefit sharing, what may count as benefits within the context of human research in Africa and the limits of the obligation of benefit sharing. Suppose the thinking about humanness, friendliness, and partiality in Afro-communitarianism were the foundation of human genetic research in Africa, then, individuals who have contributed to research or borne its burden would benefit from its rewards. This is even more important if participants have pressing needs that researchers and/or research institutions can help ease. A failure to aid sample contributors and data providers in need when researchers and research institutions can – as well as an indifference to the serious needs of contributors – are failures to exhibit friendliness in the relevant ways. Finally, though providing benefits to contributors can be an important way of showing humanity to them, nonetheless, this obligation is not absolute and may be limited by the stronger obligation of shared experience - to advance science. Studies are still required to inquire how well these norms will work in practice and inform regulatory and legal frameworks